Could Immunonutrition Help in the Fight against COVID-19 in Cancer Patient?. (21st April 2022) - Tang, Gang; Zhang, Linyu; Huang, Wang; Wei, Zhengqiang
Abstract: The rapid and widespread global pandemic of 2019 coronavirus disease (COVID-19) has had unprecedented negative health and economic impacts. Immune responses play a key role in the development of COVID-19, including the disruption of immune balance and cytokine storms caused by excessive inflammatory responses. Due to the effects of cancer itself and treatment, patients often accompanied by immunosuppression appear to be a susceptible population for COVID-19. Worryingly, COVID-19 with cancer is associated with a poor prognosis. Cancer patients are a vulnerable group, threatened by COVID-19, finding a way to combat COVID-19 for them is urgent. Immunonutrition is closely related to balance and strong immune function. Supplementary immunonutrition can improve the immune function and inflammatory response of cancer patients after surgery, which provides evidence for the role of immunonutrition in combating COVID-19. We reviewed possible mechanisms of immunonutrition against COVID-19, including enhancing immune cell function, increasing immune cell count, ameliorating excessive inflammatory response, and regulating gut microbiota. Immunonutrition supplementation in cancer patients may be beneficial to enhance immune function in the early stage of COVID-19 infection and control excessive inflammatory response in the late stage. Therefore, immunonutrition is a potential strategy for the prevention and treatment of COVID-19 in cancer.